INTEGRATED GAS-LIQUID SEPARATOR-REACTOR FOR DETERMINATIONSn(lI) AT TRACE LEVELS IN SOLUTION Reaktor Separator Gas-Cair Terintegrasi untuk Penentuan Sn(lI) pada Level Renik dalam Larutan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
ABSTRACT The determination of Sn(lI) ion at trace levels using integrated gas-liquid separator-reactor with hydride generation-quartz furnace atomic absorption spectrophotometer (HG-QFAAS) has been done. This modified gasliquid separator at various sizes was able to increase sensitivity in the determination of Sn(lI) in solution. The acid reagent mixing techniques, sample and reductant optimally occurs in a coil reaction before they are going to the gasliquid separators. The optimum conditions of parameter measurementin the determinationof Sn ion with HG method are influenced by type and concentration of acid, and the concentration of reductant has been evaluated. This optimum parameters can increase of analytical performance simultantly, which is shown by detection limit 3.74 J.lgCI for 100J.lLinjection volume (3.74 pg Sn). The accuracy of measurementshown by the % recovery of the Sn determination in natural water sample at > 95%, indicate this technique is good to be applied for tin analysis at picogram level. Keywords: Sn, hydride generation, gas-liquid reactor separator, QFAAS